Energy assessment of BIPV system in code-compliant residential building in cooling-dominated climates - Saleh H. Alyami; Noman Ashraf; Fahad M. Alyami; Ali Alhamami (PLoS ONE, 2025)
This study investigates the effects of climate and geographical location on the building integrated photovoltaics (BIPV). An existing residential building was simulated by using IES-VE software for five different climatic zones of Saudi Arabia, which was in accordance with ASHRAE Standard 169–2021 and Saudi Building Codes (SBC) 601/ 602. The results showed that the annual energy production of rooftop PV systems ranged from 49,810.29 kWh to 60,204.29 kWh, with cities such as Najran and Tabuk having higher energy production due to higher solar radiation and better performance of PV systems. The average annual global radiation ranged from 188.15 kWh/m2 to 212.52 kWh/m2, with cities such as Najran and Tabuk having the highest radiation levels. The study found that solar radiation, temperature, cloud cover and regional climate patterns significantly influence monthly energy generation, with cities closer to the equator experiencing higher solar radiation and longer daylight hours. The study also highlighted the importance of considering angular, spectral, temperature and low radiation losses, which range from 2.47% to 2.71%, 0.84% to 1.36% and 8% to 15.4%, respectively for the studies locations. This study would shed light on the impact of climate and location on the performance of PV systems and would therefore be of great interest to policy makers, energy planners and solar industry professionals to make informed decisions about the deployment of rooftop PV systems in different climate regions meet. Enabling a more sustainable energy strategy and a successful transition to a low-carbon future.